160k views
8 votes
What is the recursive formula for the sequence defined by the explicit equation an = -6 + 3n?​

What is the recursive formula for the sequence defined by the explicit equation an-example-1

2 Answers

7 votes

Answer:

an=an-1

Explanation:

as it doesnt have -6 +3n

User Oikonomiyaki
by
5.0k points
5 votes

The recursive formula for the sequence defined by the explicit equation an = -6 + 3n is an = aₙ₋₁ + 3.

The recursive formula for the sequence defined by the explicit equation an = -6 + 3n is an = aₙ₋₁ + 3.

This means that each term in the sequence is equal to the previous term plus 3. To find a specific term, you can start with the first term (a1), which is -6. Then, you can use the recursive formula to find the next term, and continue this process to find any term in the sequence.

User RepeatUntil
by
4.4k points